Promotion of Tourist Destinations of the Russian Federation on the International Market - POGREBOVA, Elena Sergeevna; ULYANCHENKO, Lyudmila Anatolyevna (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT The development of international tourism in many countries has had great impact on economic growth, the increase of employment allowed the improvement of budget revenues, solving environmental issues. With a wide variety of contemporary tourism, its role is constantly expanding. To determine the main development trends in the tourism industry in a particular country, it is necessary to take into account global trends and the consequences of globalization. Having become one of the largest export industries, tourism plays a major role in redistributing total income and foreign investment. In this regard, many countries set a goal to ensure the accelerated and balanced development of the tourism industry. RESUMEN El desarrollo del turismo internacional en muchos países ha tenido un gran impacto en el crecimiento económico y el aumento del empleo permitió mejorar los ingresos presupuestarios y resolver problemas ambientales. Con una amplia variedad de turismo contemporáneo, su papel se expande constantemente. Para determinar las principales tendencias de desarrollo en la industria del turismo en un país en particular, es necesario tener en cuenta las tendencias mundiales y las consecuencias de la globalización. Al convertirse en una de las industrias de exportación más grandes, el turismo juega un papel importante en la redistribución del ingreso mundial total y la inversión extranjera. En este sentido, muchos países establecieron un objetivo para garantizar el desarrollo acelerado y equilibrado de la industria del turismo.